Eksplorasi Kualitas Hidup dan Kepercayaan Obat terhadap Ketidakpatuhan Pasien Hemodialisis - Suryaman, Sulistia; Cholisoh, Zakky (Journal of Pharmaceutical and Sciences, 2025)
Background: Poor medication adherence is common among hemodialysis patients and is associated with adverse clinical outcomes. However, factors such as health-related quality of life (QoL) and medication beliefs remain underexplored as determinants of non-adherence in this population. Objective: This systematic review aims to synthesise the evidence regarding the relationship between QoL, medication beliefs, and pharmacological non-adherence in patients undergoing hemodialysis (HD). Methods: A comprehensive literature search was conducted using electronic databases (PubMed, Scopus, and Google Scholar) for observational studies published between January 2015 and July 2, 2025. Studies were included if they involved adult hemodialysis patients and examined QoL and/or medication beliefs concerning pharmacological non-adherence. Results: Six observational studies, encompassing 1,698 hemodialysis patients from various countries, met the inclusion criteria. The synthesised evidence indicated that poorer QoL (particularly depression and poor sleep quality), higher burden of physical symptoms, and specific medication beliefs (e.g., concerns about side effects and low perceived necessity of medications) were significantly associated with increased non-adherence. Conclusion: Non-adherence among hemodialysis patients is influenced by the complex interaction of psychosocial factors, including QoL and individual medication beliefs. To improve adherence, interventions should be developed to target these factors through health education, psychological support, and patient-centred care. Further integrative and contextual research is needed to strengthen understanding and develop more effective interventions.